Effect of Ceramic and Composite Thickness on Masking of Discoloration - Emamieh, Shila; Sabouri-majd, Yeganeh; Ghasemi, Amir (Journal of Dental School, 2021)
Objectives Color of ceramic veneers is affected by the thickness and translucency of ceramics as well as the color of the underlying tooth structure. This study aimed to assess the effect of ceramic and composite systems with two different thicknesses on masking of a substrate with C4 color shade. Methods In this in vitro, experimental study, 90 discs measuring 8 mm in diameter and 0.8 mm and 1.2 mm in thickness were fabricated from IPS e.max Press ceramic with high (HO) and low (LT) translucency, and IPS Empress Direct composite with A1 enamel and dentin shades. The samples were separately placed over a C4 substrate, and the CIE L*a*b* color parameters and color change (∆E) were measured for the seven groups using a spectrophotometer. Data were analyzed using one-way ANOVA, Tukey’s HSD test, and two-way ANOVA. Results Type of material had no significant effect on ∆E (P=0.086), and the ∆E of ceramic and composite was the same while the mean ∆E in 0.8 mm bilayer samples was significantly higher than that of 1.2 mm bilayer samples (P=0.002). The interaction effect of type of material and thickness on ∆E was not significant (P=0.113). Conclusion The masking ability is not influenced by the type of material, but thickness of material and degree of translucency affect it. None of the tested materials could completely mask the underlying color, and selection of a material for this purpose should be based on clinical conditions.